2006
DOI: 10.1016/j.cardiores.2005.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae and caveolin in transmembrane signaling: Implications for human disease

Abstract: The identification of various signaling molecules found within caveolae and their functional interaction with the integral membrane protein caveolin, a major structural component of caveolae, suggests that these membrane microdomains participate in transmembrane signaling. Several lines of evidence indicate that caveolin may act as a scaffolding protein by direct interaction with and modulation of the activity of multiple signaling molecules. The compartmentation of various signaling molecules in caveolae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 87 publications
0
66
0
4
Order By: Relevance
“…We next analyzed the effects of ozone inhalation on expression of Cav-1, a membrane scaffolding protein known to negatively regulate PI3K and p44/42 MAPK (Williams and Lisanti, 2004;Schwencke et al, 2006). Western blot analysis revealed that alveolar macrophages from air exposed wild type mice constitutively expressed Cav-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next analyzed the effects of ozone inhalation on expression of Cav-1, a membrane scaffolding protein known to negatively regulate PI3K and p44/42 MAPK (Williams and Lisanti, 2004;Schwencke et al, 2006). Western blot analysis revealed that alveolar macrophages from air exposed wild type mice constitutively expressed Cav-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is considerable evidence of caveolin involvement in the modulation of insulin signalling and therefore in the regulation of the intermediary metabolism, which becomes altered in obesity, and associated with metabolic disorders such as insulin resistance and type 2 diabetes [7]. For instance, Cav-3 deficient mice develop late-onset obesity accompanied by insulin resistance in key peripheral tissues and abnormal lipid metabolism [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The caveolae mediate non-clathrin-dependent endocytosis, and regulate the internalization of particles such as viruses and bacteria (15,16). Caveolin-1 (cav-1), a 21-to 24-kD protein, is a major resident scaffolding protein constituent of caveolae that participates in vesicular trafficking and signal transduction events (14,17,18). Cav-1 has been reported to reduce cell growth and increase apoptosis by inhibiting the activation of growth factor receptors and their downstream signaling pathways (14,17,19).…”
mentioning
confidence: 99%
“…Caveolin-1 (cav-1), a 21-to 24-kD protein, is a major resident scaffolding protein constituent of caveolae that participates in vesicular trafficking and signal transduction events (14,17,18). Cav-1 has been reported to reduce cell growth and increase apoptosis by inhibiting the activation of growth factor receptors and their downstream signaling pathways (14,17,19). In addition, cav-1 negatively regulates smooth muscle cell proliferation (20,21), and arrests mouse embryonic fibroblasts in the G0/G1 phase (22).…”
mentioning
confidence: 99%